The Effect of Service Quality and Hajj Financing on Customer Satisfaction at the Bank Muamalat Indonesia Kediri Branch Office Company - Anjely Priwindhasari, Echa; Sri Aliami (Universitas Nusantara PGRI Kediri, 2025)
Research aim : To determine the effect of service quality and Hajj financing partially and simultaneously on the level of customer satisfaction at Bank Muamalat Indonesia Kediri Branch Office. Design/Methode/Approach : This research is descriptive research with a quantitative approach. Data collection techniques by distributing questionnaires to 30 customers online via google form. The data analysis technique uses multiple linear regression after going through the classical assumption test. Research Finding : The results of the study prove that service quality affects satisfaction, Hajj financing affects satisfaction, service quality and Hajj financing simultaneously affect customer satisfaction at Bank Muamalat Indonesia Kediri Branch Office. Theoretical contribution/Originality : This research provides insight into the development of science in the form of theoretical studies, especially related to service quality and Hajj financing that can affect customer satisfaction levels. Practitionel/Policy implication : This research can be used as one of the materials in the decision making of Bank Muamalat leaders in designing marketing strategies and as a basis for designing customer service formulations, as well as making it easier to formulate prices related to the transparency of Hajj financing, so that customers really get the value of satisfaction in totality. Research limitation : The intensity of research time, the elaboration of indicators into research instruments, research subjects of 30 customers at Bank Muamalat, research studies only focus on satisfaction influenced by service quality and financing in the context of price, and in the process of collecting data through questionnaires sometimes does not show the actual opinion of respondents, so that research results cannot be generalized